(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
Tannery effluents are one of the major sources of environmental pollution with various toxic parameters and the effluent generated during liming and pickling operations of leather processing are even more dangerous due to their high and low pH range, respectively. In the present work, liming and pickling streams generated during the production of chrome tanned cow hide shoe upper was treated at different ratios and optimized the pH range 6.5 - 7.5. The effluents were mixed at different ratios without adding any foreign chemicals and obtained the results 88% reduction of COD, 94% reduction of BOD and 97% removal of total solids. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21348 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 235-239, 2014